Effect of sarcoptic mange treatment on growth performance of pigs - E Wooten-Saadi; A B Broce; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1986)
Growth performance of 135 sarcoptic mange mite-infested pigs (8 pens of 15-20 pigs each) was evaluated for an 8-week period during June-August, 1985. Pigs in 6 pens were treated with the acaricide TAKTIC EC, whereas two pens were maintained as nontreated controls. Results indicated that although treatment for sarcoptic mange was effective, it did not improve average daily gains in TAKTIC EC-treated pigs.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Sarcoptic mange treatment; Growth; Performance